Particle Beam Radiation Therapy for Skull Base Sarcomas - Yang, Jing; Hu, Weixu; Guan, Xiyin; Hu, Jiyi; Gao, Jing; Qiu, Xianxin; Huang, Qingting; Zhang, Wenna; Kong, Lin; Lu, Jiade J. (Frontiers in Oncology, 2020)
BACKGROUND: To report the clinical experience of carbon-ion and proton radiation therapy for skull base sarcomas. METHODS: An analysis of the retrospective data registry from the Shanghai Proton and Heavy Ion Center for patients withskull base sarcomas was conducted. The 1-/2-year local relapse-free, distant metastasis-free, progression-free, and overall survival (LRFS, DMFS, PFS, OS) rates as well as associated prognostic indicators were analyzed. Radiotherapy-induced acute and late toxicities were summarized. RESULTS: Between 7/2014 to 5/2019, 62 patients with skull base sarcomas of various subtypes received carbon-ion radiation therapy (53), proton radiation therapy (5), or proton radiation therapy + carbon-ion boost (4). With a median follow-up of 20.4 (range 2.73-91.67) months, the 1-/2-year OS, LRFS, DMFS, and PFS rates were 91.2%/80.2%, 89.2%/80.2%, 86.0%/81.1%, and 75.8%/62.9%, respectively. Grade 3 mucositis and grade 4 hemorrhage were observed in 1 patient for each. Only grade 1 and grade 2 toxicities were observed except for the same patient with grade 4 acute toxicity died of severe hemorrhage (grade 5). Multivariate analyses revealed the lack of prior RT was an independent favorable prognostic factor for OS, PFS, and LRFS, age under 40 was associated with improved OS, early T-disease (T1/2) showed a significant association with better PFS. CONCLUSION: With few observed acute and late toxicities, particle beam radiation therapy provided effective tumor control and overall survival for patients with skull base sarcomas.